2019
DOI: 10.1101/684670
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Graphene Quantum Dot Oxidation Governs Noncovalent Biopolymer Adsorption

Abstract: AbstractThe graphene quantum dot (GQD) is a carbon allotrope with a planar surface amenable for functionalization and nanoscale dimensions that confer photoluminescent properties. Collectively, these properties render GQDs an advantageous platform for nanobiotechnology applications, including as optical biosensors and delivery platforms. In particular, noncovalent functionalization offers a route to reversible modification and preservation of the pristine GQD substrate. However… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…While SWCNTs are reported to quench the fluorescence of GQDs, investigating the change in the fluorescence of SWCNTs when conjugated with GQDs is lacking. Jeong et al28 recently demonstrated that GQDs could interact with ssDNA strands depending on their oxidation level; ssDNA was adsorbed on the surface of GQDs with no or low oxidation, while no adsorption occurred in GQDs with medium and high oxidation levels. To avoid the interactions between GQDs and ssDNA, we synthesized three different types of mediumoxidation GQDs, compared their influence on the QY of ssDNA-SWCNTs of different chiralities, and explored the related mechanisms.…”
mentioning
confidence: 99%
“…While SWCNTs are reported to quench the fluorescence of GQDs, investigating the change in the fluorescence of SWCNTs when conjugated with GQDs is lacking. Jeong et al28 recently demonstrated that GQDs could interact with ssDNA strands depending on their oxidation level; ssDNA was adsorbed on the surface of GQDs with no or low oxidation, while no adsorption occurred in GQDs with medium and high oxidation levels. To avoid the interactions between GQDs and ssDNA, we synthesized three different types of mediumoxidation GQDs, compared their influence on the QY of ssDNA-SWCNTs of different chiralities, and explored the related mechanisms.…”
mentioning
confidence: 99%